Primary Extra Nodal Diffuse Large B-Cell Lymphoma of the Maxillary Sinus with Symptoms of Acute Pulpitis - Jian-tong Cui; Shao-qing Zhang; Hui-xia He (Case Reports in Dentistry)
Diffuse large B-cell lymphoma not otherwise specified (DLBCL-NOS) is a subtype of large B-cell non-Hodgkin lymphoma with various clinical and pathological manifestations. DLBCL-NOS which primarily arises from maxillary sinus is rare and hard to diagnose due to unique anatomy. Here, we present a case of DLBCL-NOS that developed in the left maxillary sinus of a 72-year-old male, who presented with severe toothache that resembled acute pulpitis. The lesion was diagnosed and treated based on radiographs, histological, immunohistological examinations, and PET-CT analysis. Despite its rare incidence, DLBCL-NOS should still be included in differential diagnoses to rule out malignancy in cases of endodontic disease.